Clinical utility of FAI and SHBG in differentiating PCOS from anovulatory cycles in adolescent girls - Özer, Emre; Taş, Demet; Çakır Gündoğan, Seçil; Boyraz, Mehmet; Gürbüz, Fatih (Frontiers in Pediatrics, 2025)
IntroductionMenstrual irregularities are common in adolescents, often linked to anovulatory cycles. This study aims to establish diagnostic cut-off values for Polycystic Ovary Syndrome (PCOS) and differentiate it from anovulatory dysfunction in adolescents, while evaluating the diagnostic sensitivity of the Free Androgen Index (FAI) and Sex Hormone Binding Globulin (SHBG).MethodsThe study included 305 adolescents with oligomenorrhea at a tertiary center. Statistical analyses were performed, and Receiver Operating Characteristic (ROC) curves were used to assess diagnostic performance.ResultsOf the 305 patients, 229 (75%) had anovulatory cycles, and 36 (11.8%) were diagnosed with PCOS. Mean FAI values were 3.5 ± 2 in anovulatory cycles, 8.0 ± 5 in PCOS, and 8.3 ± 4 in hyperinsulinism (p < 0.001). FAI showed significant positive correlations with HOMA-IR (r = 0.389, p < 0.001) and BMI z-score (r = 0.499, p < 0.001). ROC analysis identified an LH threshold of 9.7 U/L and an LH/FSH ratio of 2.62 as predictive markers for PCOS.DiscussionAnovulatory cycles are the leading cause of menstrual irregularities in adolescents. While hyperandrogenism is crucial for PCOS diagnosis, elevated FAI levels in PCOS are also observed in hyperinsulinemia and obesity. PCOS is more prevalent in obese adolescents, which limits the diagnostic reliability of FAI. Lower SHBG levels in hyperinsulinemic obese adolescents further complicate FAI interpretation, underscoring the significant impact of glucose and insulin metabolism on these markers. Therefore, a comprehensive diagnostic approach, including androgen levels, LH/FSH ratio, SHBG, FAI, and ovarian ultrasound, is essential for accurate PCOS diagnosis in adolescent girls.